Examining well-being among non-academic university staff in Malaysia during Covid-19 pandemic - D’Silva, Jeffrey Lawrence; Ismail, Ismi Arif; Abdul Rahman, Haliza; Ahmad Ghazali, Akmar Hayati; Mohd Zain, Mohd Izani; Hamsan, Hanina Halimatusaadiah; Arshad, Mohd Mursyid; Mohamed Shaffril, Hayrol Azril; Dahalan, Dzuhailmi; Kamarudin, Nurul Akhtar (Human Resource Management Academic Research Society, 2022)
During the Covid-19 pandemic, employee well-being including non-academic university staff had an impact as staff adapted to working with a different setting. Till now there has been very few empirical research to determine the level of well-being among non-academic university personnel even though this group occupies a vast majority of workforce in a university. As a result, this study investigated the status of well-being among non-academic university staff attached to a Malaysian institution of higher learning. The study was quantitative in nature and the survey instrument was developed based on previous research and nominal group technique. The total number of respondents that took part in this study was 1,759, and the data was collected through an online platform. Overall, the findings revealed that the well-being index for non-academic staff at the institution was 77.2%, indicating that they are typically moderately happy at work. Based on the findings, improving the work environment, career growth, and reduction in workload should be prioritised to promote well-being among non-academic university staff.